Piscine orthoreovirus can infect and shed through the intestine in experimentally challenged Atlantic salmon (Salmo salar L.). (December 2016) - Hauge, Helena; Dahle, Maria; Moldal, Torfinn; Thoen, Even; Gjevre, Anne-Gerd; Weli, Simon; Alarcón, Marta; Grove, Søren
Abstract Piscine orthoreovirus (PRV) is a ubiquitous virus in Norwegian salmon farms associated with the disease heart and skeletal muscle inflammation (HSMI). Experimental challenge has shown that the virus replicates in circulating red blood cells of Atlantic salmon prior to infecting heart myocytes. The infection route from water to blood is however still unknown. The related mammalian orthoreovirus primarily infects the lungs and gastrointestinal (GI) tract and is proposed to spread mainly through the faecal–oral route. To investigate the role of the salmonid GI tract in PRV-infection, oral and anal administration of virus was compared to intraperitoneal (i.p.) injection. When administered anally, PRV was transferred to blood 4 days post challenge (dpc) and levels peaked at 42 dpc, similar to i.p. injected fish. PRV was detected in heart and faeces with corresponding kinetics, and inflammatory heart lesions consistent with HSMI were observed from 49 dpc. The orally intubated group showed slower virus kinetics in both blood and heart, and no signs of HSMI. Compared to the oral and i.p. administration routes, leakage of virus inoculate by anal intubation was minor and challenge was restricted to the mid- and distal intestine. These findings show that anal intubation is an efficacious method for PRV delivery to the GI tract and demonstrates that PRV can establish infection through the intestine with the potential for transmission via faeces.